Outcomes predictors in endoscopic ultrasound-guided choledochoduodenostomy with lumen-apposing metal stent: Systematic review and meta-analysis - Fugazza, Alessandro; Khalaf, Kareem; Spadaccini, Marco; Facciorusso, Antonio; Colombo, Matteo; Andreozzi, Marta; Carrara, Silvia; Binda, Cecilia; Fabbri, Carlo; Anderloni, Andrea; Hassan, Cesare; Baron, Todd; Repici, Alessandro (Endoscopy International Open, 2024)
Background and study aims EUS-guided choledochoduodenostomy (EUS-CDS) is a minimally invasive procedure used to treat malignant biliary obstruction (MBO) by transduodenal placement of a lumen-apposing metal stent (LAMS) into the extrahepatic bile duct. To identify factors that contribute to safe and effective EUS-CDS using LAMS, we performed a systematic review of the literature and meta-analysis.Methods The methodology of our analysis was based on PRISMA recommendations. Electronic databases (Medline, Scopus, EMBASE) were searched up to November 2022. Full articles that included patients with distal malignant biliary obstruction who underwent EUS-CDS using LAMS after failed endoscopic retrograde cholangiopancreatography were eligible. Random-effect meta-analysis was performed reporting pooled rates of technical success, clinical success, and adverse events (AEs) by means of a random model. Multivariate meta-regression and subgroup analysis were performed to assess possible associations between the outcomes and selected variables to assess the correlation between outcomes and different variables. Results were also stratified according to stent size.Results Twelve studies with 845 patients were included in the meta-analysis. Pooled technical and clinical success rates were 96% (95% confidence interval [CI] 94%-98%; I2 = 52.29%) and 96% (95%CI 95%-98%), respectively, with no significant association with baseline characteristics, such are sex, age, common bile duct diameter, or stent size. The pooled AE rate was 12% (95%CI: 8%-16%; I2 = 71.62%). The AE rate was significantly lower when using an 8 × 8 mm stent as compared with a 6 × 8 mm LAMS (odds ratio 0.59, 0.35–0.99; P = 0.04), with no evidence of heterogeneity (I2 = 0%).Conclusions EUS-CDS with LAMS is a safe and effective option for relief of MBO. Selecting an appropriate stent size is crucial for achieving optimal safety outcomes.
Keywords: Pancreatobiliary (ERCP/PTCD); Biliary tract; Endoscopic ultrasonography; Intervention EUS